Globalization and trade flows: What you see is not what you get! - Andreas Maurer; Christophe Degain (World Trade Organization (WTO), 2010)
The trade collapse that followed the recent financial crisis has led to a renewed interest on the measurement issues affecting international merchandise trade statistics in the new globalized economy. The international fragmentation of industrial production blurs the concept of country of origin and calls for the production of new statistics on the domestic content of exports, with a view of estimating trade in value added. Alongside, the international statistical community has revised in 2010 the concepts and definitions on both, international merchandise trade and trade in services statistics. This paper discusses the various issues related to the concepts of goods for processing and intra firm trade in trade statistics, and provides an overview of the method of analysing the impact of the fragmentation of production in international value chains.
Keywords: C49; F13; F23; F49; 330; trade statistics; goods for processing; intra-firm trade; trade in intermediate products; trade in value added; Intraindustrieller Handel; Außenhandelsstatistik; Statistische Methode